2018
DOI: 10.1021/acs.jced.8b00625
|View full text |Cite
|
Sign up to set email alerts
|

Vapor–Liquid Equilibrium, Volumetric, and Compressibility Properties of 1-Propanol + Poly(ethylene glycol) Dimethyl Ether 250 and 500 Binary Mixtures

Abstract: In this work, some of the thermodynamic properties of binary {1-propanol + poly­(ethylene glycol) dimethyl ether (PEGDME)} mixtures were studied. The activity of 1-propanol was determined in (1-propanol + PEGDME) systems with polymer molar masses of 250 and 500 g·mol–1 by the use of isopiestic method at 298.15 K. The effect of the polymer molar mass on the solvent activity and also vapor pressure depression was discussed. More vapor pressure lowering is obtained when we use PEGDME with a molar mass of 500 g·mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…To have a clear picture in regard to the hydration of studied polymers in aqueous media, vapor pressure depression values, Δ p , were determined In Figure , Δ p values for (PPG 400 + H 2 O) and (PEGDME 250 + H 2 O) systems plotted against the mass fraction of polymers are illustrated at T = 298.15 K. It is observed that Δ p values for the (PEGDME 250 + H 2 O) solution are higher than those for the (PPG 400 + H 2 O) solution at the equal mass fractions of polymers, which indicate that there are stronger interactions between PEGDME 250 with water compared to PPG 400 .…”
Section: Resultsmentioning
confidence: 99%
“…To have a clear picture in regard to the hydration of studied polymers in aqueous media, vapor pressure depression values, Δ p , were determined In Figure , Δ p values for (PPG 400 + H 2 O) and (PEGDME 250 + H 2 O) systems plotted against the mass fraction of polymers are illustrated at T = 298.15 K. It is observed that Δ p values for the (PEGDME 250 + H 2 O) solution are higher than those for the (PPG 400 + H 2 O) solution at the equal mass fractions of polymers, which indicate that there are stronger interactions between PEGDME 250 with water compared to PPG 400 .…”
Section: Resultsmentioning
confidence: 99%